Secure Document Fragmentation Tool with Two Layers of Encryptions: SecDoc - Abdul Halim, Armisha Hazrin Fitri; Chuah Chai Wen, (Applied Information Technology And Computer Science, 2022)
Electronic document sharing through an email attachment is the main communication platform in a corporate setting. As it is a convenient way to share information. However, sharing documents through email attachments required security. This is because of the fact that email is never intended to be a secure channel for sending information. There are various types of email attacks. Attackers may intercept the network traffic and steal the data. Confidentiality of sensitive information can be abused. As a result, sensitive data or information should be protected before it is sent in an email as an attachment. Thus, the electronic document must be protected before it is transferred. In this project, fragmentation and hybrid encryption tool are proposed to provide additional security to the electronic document. Fragmentation is used to break off a document into a fragment that has no understandable meaning. Hybrid encryption is the combination of symmetric and asymmetric encryption using AES (Advanced Encryption Standard) and RSA (Rivest-Shamir-Adleman) to encrypt the fragmented document for making it more secure. In a nutshell, the SecDoc assists users to protect sensitive data of their valuable documentation from illegal third-party users. The methodology chosen for this project is Object-Oriented Software Development (OOSD). The proposed tool is developed using Java programming language. The tool has five main modules. The tool allowed users to select, split, encrypt, decrypt, and join the desired documents before it is attached to an email.  The key entered by the users is saved in a file and the key file is encrypted with the user’s public key. Overall, the developed tool is able to protect the confidentiality of sensitive documents.